2021
DOI: 10.3389/fonc.2021.719638
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Predictive Scoring System for Colorectal Cancer Patients With Liver Metastasis: A Population-Based Study

Abstract: Liver metastasis in colorectal cancer (CRC) is common and has an unfavorable prognosis. This study aimed to establish a functional nomogram model to predict overall survival (OS) and cancer-specific survival (CSS) in patients with colorectal cancer liver metastasis (CRCLM). A total of 9,736 patients with CRCLM from 2010 to 2016 were randomly assigned to training, internal validation, and external validation cohorts. Univariate and multivariate Cox analyses were performed to identify independent clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Distant organ metastasis (mainly to the liver) is a clinical hallmark of young-onset CRC, accounting for most of the deaths [ 11 ]. Multiple liver metastases, nodules, the degree of differentiation, extrahepatic metastasis, tumor size, CEA level, positive surgical margins, and venous infiltration are all significant predictors of CRLM patient survival [ 12 , 13 , 14 ]. However, clinicopathological characteristics differ significantly between younger and older CRC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distant organ metastasis (mainly to the liver) is a clinical hallmark of young-onset CRC, accounting for most of the deaths [ 11 ]. Multiple liver metastases, nodules, the degree of differentiation, extrahepatic metastasis, tumor size, CEA level, positive surgical margins, and venous infiltration are all significant predictors of CRLM patient survival [ 12 , 13 , 14 ]. However, clinicopathological characteristics differ significantly between younger and older CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Young-onset CRLM patients with rectal and left colon tumors had better outcomes than those with right colon tumors, but there was no significant difference between patients with rectal and left colon tumors. According to a previous study based on the SEER database, CRLM patients with colon primaries had worse survival than those with rectal primaries [ 14 ]. Different from our findings, this suggests that young-onset CLRM patients may have unique prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, conventional TNM staging often fails to accurately predict patient prognosis. The results of a previous study showed that the maximum AUC value of 5-year OS for patients with CRCLM was 0.627, indicating that TNM staging is not su cient to meet the clinical needs of a speci c population and cannot accurately predict prognosis in CRCLM [39]. In the present study, a clinical prediction model was established based on the results of multivariate cox analysis, and the AUC for 5-year OS reached 0.744.…”
Section: Discussionmentioning
confidence: 59%
“…TBS was defined as the distance from the origin of a Cartesian plane using maximum tumor size as the X-axis and tumor number as the Y-axis (9). As previously reported, TBS is a valuable tool in evaluating prognosis for colorectal liver metastases, HCC, and ICC (13,26,27). The present study assessed the significance of TBS in dictating the prognosis of patients with cHCC-CCA after curative liver resection.…”
Section: Discussionmentioning
confidence: 77%